Prevalence of different types of cancer in Tertiary Level Hospital of Nepal - Mahaseth, Rita Kumari; Upadhyaya, Rashika; Bhetwal Sapkota, Bharati; Karki, Anil Bikram; Shah, Gurusharan (Nepalese Journal of Cancer, 2025)
Introduction: Cancer continues to be the leading cause of death in developed countries and the second leading cause of death in developing nations despite the advancements in curative and therapeutic methods. Hence, this study aims to find out the prevalence of cancer in Tertiary Level Hospital of Nepal and identify the most prevalent cancer amongst the different age groups and sexes.Methods: This is a retrospective hospital-based study which included a total of 580 patients diagnosed with cancer who visited the Oncology and Pathology Department at Nepal Medical College and Teaching Hospital from April 2021 to March 2024. Data was retrieved from the records and files that contained informations about the patients diagnosed with cancer. The data was analyzed utilizing SPSS version 16.0.Results: Among the total of 580 patients, cancer was most prevalent in 60-80 years age group, representing 42.24% of cases, while females made up the majority of diagnosed patients at 53.28%. Furthermore, stomach cancer is the most prevalent type of cancer, comprising 14.83% of cases, closely followed by lung cancer at 14.48%. Most of the cancer types demonstrate a significantly higher prevalence among individuals over 40 years of age, with 94.05% of lung cancer cases, 86.05% of stomach cancer cases, and 100% of cervical carcinoma cases occurring in this age group.Conclusions: The findings of this study reveal a significant prevalence of cancer among older adults which suggests that the aging population is particularly vulnerable and may require enhanced cancer awareness and screening initiatives. This trend presses the need for targeted cancer prevention and treatment strategies tailored to older populations, focusing particularly on the most prevalent types of cancer identified in the study. This approach could significantly improve health outcomes and resource allocation within healthcare systems.